Het Gouden Paviljoen : De Warande. - Nagels, Annelies; Segers, Dries (Turnhout : De Warande, 2018)
Vervaet, Filip ; Van Dijck, Hannelore ; Tirelli, Marco ; De Brucykere, Berlinde ; Bru, Lucia ; Nicolodi, Renato ; Segers, Dries ; Dekyndt, Edith ; Van Imschoot, Jan ; Muller, Sofie ; Gerhard, Tatjana ; Goiris, Geert ; Jaber, Athar ; Devos, Danny ; Rumando, Tokyo ; Vandenberg, Philippe ; Yokota, Daisuke ; Green, Gregory ; Farrow, Al ; Copers, Leo ; Gersht, Ori
Het Gouden Paviljoen, de Warande, Turnhout, 11 maart t.e.m. 20 mei 2018
boek